Usulan Perbaikan Tata Letak Menggunakan Metode Systematic Layout Planning dan CRAFT PT. XYZ - Alexander, Muhammad Luigi; Fitria, Lisye (e-Proceeding FTI, 2024)
PT XYZ will conduct a facility layout redesign using the Systematic Layout Planning (SLP) and Computerized Relative Allocation of Facilities Technique (CRAFT) methods to reduce material handling costs. The current factory layout exhibits irregular machine placements, limited space, and machine interconnections that do not follow the flow of processes. The analysis results from these methods indicate a reduction in the distance of movements and a decrease in material handling costs on the company’s production floor. The existing layout is proven to be inefficient in terms of material flow, with a total product movement distance of 124.75m. The proposed SLP layout successfully reduces the total distance to 99.91m. Furthermore, the CRAFT analysis shows a more significant reduction in the total distance, reaching 95.01m, resulting in cost savings with a reduction from Rp 798,977 in the existing layout to Rp 523,393 in the proposed CRAFT layout. This research confirms that the existing layout is inefficient in terms of movement distance, and the redesign using SLP and CRAFT methods proves to be effective in reducing the movement distance. Keywords: Production Layout, Systematic Layout Planning, Computerized Relative Allocation of Facilities Technique, Cost Material Handling. PT XYZ akan melakukan perancangan ulang tata letak fasilitas dengan metode Systematic Layout Planning (SLP) dan Computerized Relative Allocation of Facilities Technique (CRAFT) untuk mengurangi ongkos material handling. Tata letak pabrik menunjukkan letak mesin yang tidak teratur, keterbatasan luas, dan hubungan keterkaitan mesin yang tidak mengacu pada aliran proses. Hasil analisis metode menunjukkan pengurangan jarak perpindahan dan pengurangan pada OMH pada lantai produksi perusahaan. Hasil dari layout eksisting terbukti boros aliran bahan dengan jarak total perpindahan produk 124,75m. Layout usulan SLP berhasil mengurangi jarak total menjadi 99,91m. Analisis CRAFT menunjukkan pengurangan jarak total yang lebih signifikan, yaitu 95,01m, dan menghemat ongkos dengan pengurangan dari Rp 798.977 layout eksisting menjadi Rp 523.393 layout usulan CRAFT. Penelitian ini membuktikan layout eksisting boros jarak perpindahan, dengan perencanaan ulang menggunakan metode SLP dan CRAFT terbukti memberi pengurangan dalam jarak perpindahan. Kata kunci: Tata Letak Produksi, Systematic Layout Planning, Computerized Relative Allocation of Facilities Technique, Ongkos Material Handling.